Similarity of graphic features in family, professional and accidental handwritten records - Zieniewicz, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
This publication concerns the problem of similarities appearing in the records of different persons, and it presents this issue in practical terms based on examples covering handwriting samples taken from members of the same family, persons pursuing the same profession, or unrelated persons. Its objective is not only to emphasise the existence of this phenomenon and its importance for opinion-making in a handwriting expert opinion process regarding the author of a handwritten transcript, but also an attempt to identify the handwriting features in which these analogies occur.
Keywords: handwriting expert opinion; handwriting analysis; handwriting features; expert